Improvement of Surface Properties of Structural Steel Using (Fe+Ti64+Gray Cast Iron) As TIG Cladding Layer - F. Kadhim, Dheyaa; H. Saddam, Falih; Sahib M. Al-hamdani, Kamaal (University of Thi-Qar Journal, 2024)
This paper presents a practical study of a mixture of cast iron, Ti-6Al-4V alloy turning flakes, and pure iron powder as a hard coating layer to improve the surface properties of structural steel. A TIG welding machine was used as the heat source to deposit the cladding metal onto the substrate surface. The process parameters for the cladding process were (100 A) and (9, 10, 11 L/min), representing the current and gas flow rate, respectively. Optical microscope, X-ray diffractometer, Vickers hardness test, and Pin on disc tribometer used to investigate the microstructure, phase composition, microhardness, and wear resistance. The results show that the cladding layers consist of FCC and BCC phases, with a small amount of other unknown phases. They also show that samples prepared under a wide range of gas flow rates have a high hardness, approximately two times that of the substrate. wear test results show that the wear rates of samples prepared under a high range of gas flow rates were 1.5 times less than the substrate